A comprehensive review on the phytochemical constituents and pharmacological activities of Pogostemon cablin Benth.: an aromatic medicinal plant of industrial importance - Sinniah, Uma Rani; Swamy, Mallapa Kumara (MDPI, 2015)
Pogostemon cablin Benth. (patchouli) is an important herb which possesses many therapeutic properties and is widely used in the fragrance industries. In traditional medicinal practices, it is used to treat colds, headaches, fever, nausea, vomiting, diarrhea, abdominal pain, insect and snake bites. In aromatherapy, patchouli oil is used to relieve depression, stress, calm nerves, control appetite and to improve sexual interest. Till now more than 140 compounds, including terpenoids, phytosterols, flavonoids, organic acids, lignins, alkaloids, glycosides, alcohols, aldehydes have been isolated and identified from patchouli. The main phytochemical compounds are patchouli alcohol, α-patchoulene, β-patchoulene, α-bulnesene, seychellene, norpatchoulenol, pogostone, eugenol and pogostol. Modern studies have revealed several biological activities such as antioxidant, analgesic, anti-inflammatory, antiplatelet, antithrombotic, aphrodisiac, antidepressant, antimutagenic, antiemetic, fibrinolytic and cytotoxic activities. However, some of the traditional uses need to be verified and may require standardizing and authenticating the bioactivity of purified compounds through scientific methods. The aim of the present review is to provide comprehensive knowledge on the phytochemistry and pharmacological activities of essential oil and different plant extracts of patchouli based on the available scientific literature. This information will provide a potential guide in exploring the use of main active compounds of patchouli in various medical fields.